Contesting Legitimacy in Extractive Landscapes: Community Resistance in Indonesia’s Sand Mining Conflict - MC Candra Rusmala Dibyorini; Aulia Widya Sakina; Anastasia Adiwirahayu; Umbu Domu Mahani (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2025)
Sand mining has become one of the fastest-growing forms of resource exploitation worldwide, driven by rapid urbanization and infrastructure development. However, its expansion has increasingly generated environmental degradation and social conflicts, particularly in riverine and volcanic landscapes where sand deposits are abundant. This study examines the dynamics of sand mining conflict in the Mount Merapi area, Indonesia, focusing on how contested legitimacy over resource control shapes community resistance and environmental governance. Using a qualitative case study of the Tringsing River, this research draws on in-depth interviews, focus group discussions, field observations, and document analysis to explore interactions among local communities, mining actors, and government authorities. The findings reveal that sand mining conflicts are not merely disputes over economic resources but reflect broader struggles over the legitimacy of governance institutions and environmental stewardship. Local communities from Sewukan, Sengi, and Paten mobilized collective resistance through the Trimanunggal Inter-Village Cooperation Agency (BKAD), which functions as a community-based environmental governance institution. Meanwhile, fragmented regulatory arrangements and overlapping authorities have weakened enforcement and complicated conflict resolution. This study highlights that grassroots resistance represents an alternative form of environmental governance and emphasizes the need for stronger institutional coordination and recognition of community-based actors.